Intellectual freedom against patriarchal society in Elizabeth Barrett Browning’s Aurora Leigh: Liberal feminism study - Dennis Audria Pramana; Ken Widyatwati; M. Suryadi (Universitas Tidar, 2026)
The study of Victorian literature is crucial in order to gain a comprehensive understanding of literary works as a medium for criticizing patriarchal social structures. In the context of this study, this is particularly relevant in terms of constructing female identity and roles. Elizabeth Barrett Browning's poem Aurora Leigh has been extensively studied in the context of feminism and gender relations. However, studies of this poem using Mary Wollstonecraft's liberal feminist perspective are relatively limited. This study aims to analyze Aurora's struggle to attain intellectual freedom and independence for women. In addition, this study also discusses her struggle to reject patriarchal norms and traditional gender roles in the Victorian era. This study employs a qualitative descriptive method with close reading techniques. The theoretical framework used in this study is Mary Wollstonecraft's liberal feminism in A Vindication of the Rights of Woman (1792). The results show that Aurora is represented as a rational woman who demands education, freedom of thought, and rejects the institution of marriage that limits her freedom. Aurora's struggle ultimately voices the principles of liberal feminism regarding rationality, education, and women's independence in a patriarchal society.